2002
DOI: 10.3758/cabn.2.4.329
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral consequences of radiation exposure to simulated space radiation in the C57BL/6 mouse: Open field, rotorod, and acoustic startle

Abstract: Two experiments were carried out to investigate the consequences of exposure to proton radiation, such as might occur for astronauts during space flight. C57BL/6 mice were exposed, either with or without 15-g/cm 2 aluminum shielding, to 0-, 3-, or 4-Gy proton irradiation mimicking features of a solar particle event. Irradiation produced transient direct deficits in open-field exploratory behavior and acoustic startle habituation. Rotorod performance at 18 rpm was impaired by exposure to proton radiation and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 75 publications
1
13
0
5
Order By: Relevance
“…Again it appears as though proton irradiation does not produce the same deleterious behavioral and neurochemical effects as 56 Fe particle irradiation. Another possible explanation for the transient effects seen by Pecaut et al (2002) following proton irradiation is that they used mice, while we used rats in the current study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Again it appears as though proton irradiation does not produce the same deleterious behavioral and neurochemical effects as 56 Fe particle irradiation. Another possible explanation for the transient effects seen by Pecaut et al (2002) following proton irradiation is that they used mice, while we used rats in the current study.…”
Section: Discussionmentioning
confidence: 90%
“…Thus far, astrocytes per se have not been shown to be implicated in learning and memory, therefore, we would not expect to see changes in the behavior measured in this study at these proton doses. Another study using C57BL/6 mice indicated that exposure to 250 MeV (3 or 4 Gy) proton irradiation produced transient direct deficits in spontaneous open-field locomotor activity, acoustic startle habituation, and rotorod performance (Pecaut et al, 2002). However, if left to recover for 2 weeks following exposure, only rotorod performance at 26 rpm was impaired (Pecaut et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The present approach combines endpoint with qualitative measures for the standard rotorod test and the novel ladder rung task. A large number of studies have used the rotorod for assessment of motor capabilities in mice, which requires the mouse to walk on a rotating drum, mainly for quantitative assessment of temporal aspects of balance and walking (Caston et al, 2003;Pecaut et al, 2002;Tillerson et al, 2002). The common endpoint measure is based on the duration that an animal stays up on the drum as a function of drum rotation speed.…”
Section: A New Test Strategy For the Assessment Of Skilled Walking Inmentioning
confidence: 99%
“…As for rodents, conditioned taste aversion could be induced at doses as low as 0.25 Gy (Bogo 1988). Interestingly, 3 Gy of proton radiation caused a decrease in latency to fall in rotarod testing and loss of acoustic startle habituation (Pecaut et al 2002). In sum, almost all studies reporting on the behavioral impact of low-dose radiation (≤10 Gy) examined endpoints of days to weeks post radiation.…”
Section: Introductionmentioning
confidence: 99%